Pengaruh Edukasi APAR terhadap Pengetahuan Penggunaan APAR pada Pekerja Produksi PT Mekar Armada Jaya - Pinta Dormiana Panjaitan; Maria Paskanita Widjanarti; Isna Qadrijadi (Sekolah Vokasi, Universitas Sebelas Maret, 2025)
PT Mekar Armada Jaya was an automotive manufacturing company. In the production process, it was assisted by work equipment in the welding production section in the form of welding and grinding tools that can cause sparks. The spark was one of the factors in the occurrence of fires. Fire extinguisher training has never been carried out and workers do not have good knowledge. One way to increase fire extinguisher knowledge was by educating fire extinguishers to production workers. The research method used was an experimental design (quasi-experiment) with a research design of one-group pretest-posttest design. Respondents were taken from welding production workers totaling 45 respondents. The sampling technique used was total sampling. Measurement of the level of knowledge of the use of fire extinguisher using questionnaires. Technical data analysis uses a non-parametric alternative test, namely the Wilcoxon test. The average result of the knowledge pretest using fire extinguisher was 8.11 and posttest 14.18. The results of the analysis on the Wilcoxon test obtained negative ranks were 0 meaning that no workers have decreased knowledge value from pretest to posttest, positive ranks are 45 workers have increased pretest scores to posttest and ties was 0 meaning that no workers have the same value between pretest and posttest. p value 0. (p-value < 0.05) shows that there was an influence of fire extinguisher education on knowledge of using fire extinguisher. There was correlation between fire extinguisher education on knowledge of the use of fire extinguisher in PT Mekar Armada Jaya production workers.